PENGEMBANGAN GREEN TOURISM DI DAYA TARIK WISATA PANTAI JERMAN, KECAMATAN KUTA SELATAN, KABUPATEN BADUNG - Bahus, Maria Nova Lorena; Sunarta , I Nyoman (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
German beach is one of the tourist attractions that is currently a tourist location that is visited by local and foreign tourists. Tourism is an attraction for tourists who visit German Beach. The problems faced in this study are the use of beach facilities, hygiene problems that are not well considered by tourists and the role of stakeholders in tourism development at German Beach has not been maximally implemented in accordance with the main objectives. Types of data and data sources, namely qualitative data Primary and secondary data. The data collection techniques used are observation, interview, and documentation. In the implementation of the German Beach development strategy as a tourist attraction that applies Green Tourism principles that lead to environmental preservation. With the condition of German Beach which is environmentally friendly still tends to be natural, the application of the principle of environmental preservation must involve local communities, governments, entrepreneurs and visiting tourists. The government, regions and villages, are obliged to issue policies on the environment, management around German Beach based on the principle of sustainability, the community, entrepreneurs and tourists participate in supervising its implementation and are directly involved in preserving the environment around Kelan Beach.